Toward a control theory of white-collar offending - Lasley, James R. (Journal of quantitative criminology, 1988)
In this study, Hirschi's control theory was conceptually developed and empirically tested as a rationale for white-collar offending. The data were gathered from a sample of 435 executives who were employees of a multinational automobile manufacturer. Results suggest that factors within the corporation such as managerial attachments, work commitment and involvement, and belief in corporate rules significantly affect individual rates of executive self-reported offending. In particular, those executives who possessed the strongest bond to their manager, their co-workers, and the corporation itself were least likely to report having engaged in a white-collar crime. Theoretical implications of these findings and how they relate to extant theories of white-collar criminality are discussed.